Development of Rice Threshing Machine Based Quality Function Deployment Approach – A Case Study - Susilawati, Anita; Roni, Guido; Yohanes, Yohanes; Anuar, Kaspul; Fatiya, Fatiya (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
Threshing rice is an important stage in agriculture, especially in rice production. The aim of this paper is to develop designs for multi-functional rice threshing machines using the Quality Function Deployment (QFD) approach. The case study was conducted on farmers in a village in Indonesia. Based on observations and survey results conducted with farmers, there was a problem with the rice threshing machine being used less than optimally, so that the time and cost of harvesting became greater. The research was carried out by collecting data by distributing questionnaires directly to 15 respondents. In this research, validity and reliability testing was carried out. The result was in the form of design development, the weight of the rice threshing machine was obtained at 35 kg, which was lighter than previously machine used by farmers. More, the development for new one was resistant to rust and has a fan that functions to separate the rice grains from the grain. Priority of technical characteristics based on weight and dual function of the tool. The dual function of the tool was to thresh and separate the rice with sides and empty ones. Furthermore, the development of rice threshing machine can tailored to the consumers needs.